The Role of Parents In Brushing Teeth With Dental Caries In Autistic Children In Slb C Autis Negeri Tuban - Asri, Abil; Marjianto, Agus; Sunomo Hadi; Sugito, Bambang Hadi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Dental caries is the damage to the hard tissues of the teeth caused by the acids present in carbohydrates through the intermediates of microorganisms present in the saliva. The prevalence of dental caries in autistic children is classified as high, because autistic children have different mental, emotional and physical limitations compared to normal children, so autistic children need the help of parents in brushing their teeth. One of the causes of dental caries problems in autistic children is that the way to brush teeth is still not right. Therefore, the role of parents in getting used to brushing their teeth is very important. Considering the importance of the relationship between the role of parents in brushing their teeth and the prevalence of dental caries in autistic children, this study aims to find out the relationship in autistic children in SLB C Autistic Tuban. This type of research is a cross sectional research. The respondents in this study were 21 parents and 21 autistic children. The analysis technique used in this study is the Rank Spearman Test correlation test with a significance level of p-value (ρ <0.05). The results of this study showed that the p-value (ρ= 0.016<0.05) which means that there was a relationship between the role of parents in brushing teeth and very high dental caries in autistic children in SLB C Autis Negeri Tuban, the role of parents as companions, supervisors, educators and drivers with a passive category.